2015
DOI: 10.1097/01.naj.0000463025.42388.10
|View full text |Cite
|
Sign up to set email alerts
|

Ce

Abstract: While much has been written about the effects of extended work hours on quality of nursing care, nurse burnout, and job attrition, the potential adverse effects of acute and chronic sleep loss on the overall health and well-being of nurses has received little attention. The author describes the acute and chronic effects of sleep loss on nurses, strategies nurses can use to increase the quantity and quality of their sleep, and institutional policies that can promote adequate rest and recuperation between work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…17 However, nurses' health-related behaviors may be influenced by the culture, structure and policies of the organization in which they are employed and by personal factors such as age, sex, marital status, emotional support, general physical health, health perception, perceived benefits or barriers to health, and a sense of confidence in the ability to make changes. 6 With the objective of describing the acute and chronic effects of sleep depravity in the nursing team, the research has identified that little attention is paid to this subject. In this sense, the authors recommend the creation of a policy that promotes better quantity and quality of sleep for these professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, nurses' health-related behaviors may be influenced by the culture, structure and policies of the organization in which they are employed and by personal factors such as age, sex, marital status, emotional support, general physical health, health perception, perceived benefits or barriers to health, and a sense of confidence in the ability to make changes. 6 With the objective of describing the acute and chronic effects of sleep depravity in the nursing team, the research has identified that little attention is paid to this subject. In this sense, the authors recommend the creation of a policy that promotes better quantity and quality of sleep for these professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of sleep suggests physical or cognitive impairment of the work practice, 5 implying alterations in memory, judgment capacity and performance of activities, associating with health problems such as obesity, diabetes mellitus, cardiovascular diseases, among other damages. 6 Excessive daytime sleepiness (EDS) is characterized as a chronic sleep symptom, an inability to stay awake and/or alert during the daytime period, 7 which can have repercussions on activities such as working, driving and socializing. 8 Sleepiness, when related to the nurses' work, has been shown to impact on patient care and safety, 8 being a condition in which there is a reduction of the work force and the quality of life, with repercussion for the life of the individual.…”
Section: Introductionmentioning
confidence: 99%
“…[3,8] College students, in particular, experience the pressing need to work and maintain social lives while balancing extensive class and study time. Hershner and Chevin [9] reported that 50% of college students suffer from daytime sleepiness, and 70% do not obtain sufficient sleep impacting grade point averages, the risk of academic failure, auto accidents, learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also found that a significant proportion of nurses and nursing students suffer from sleep abnormalities and associated medical issues (headaches, tiredness, back pain, gastroesophageal reflux, insomnia, and depression), as well as lower grades in those with significant lack of sleep. [3,10,11] Additionally, the circadian system of young people supports late nights for sleeping and late mornings or early afternoons for waking. Daytime sleepiness due to lack of natural sleep reduces academic achievement, learning, and behavioral performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation